Plantas indicadoras do rebaixamento do nível do aquífero freático, em veredas do Cerrado de Mato Grosso - Lanoa, Angela Dabela (2012)
This paper seeks to know the succession of plant species belonging to the cerrado sentido restrito that enter an area campo limpo úmido that has the level of groundwater table lowered. Transects were installed three A, B and C. In an average slope of hill, on top of Cerrado vegetation is restricted sense, a wet field toward the course of water. The area is located in Samambaia and Fim da Picada Farms in Chapada dos Guimarães, Mato Grosso. Transects A and B were implanted in local and state C was kept in an environment that is linear with erosion phenomena pipping. It was made monitoring variations in rainfall from September 2010 to December 2011, of water level of soil, soil classification and floristic. Due to the lowering of the water table there were changes in the vegetation transect C, such as the predominance of Pteridium aquilinum and Simarouba versicolor. Soil type and Plintosolo Plintosolo Pétrico advance by soil where there was hidromórfico cinzento and Glei úmido.